Green meets food delivery services: consumers' intention to reuse food delivery containers in the post-pandemic era - Sia, Joseph; Ho, Jie Min; Hii, Ivy (2023)
Purpose: The coronavirus disease (COVID-19) has increased food delivery service demand, which generates massive amounts of solid waste, specifically plastic material. Therefore, this study aims to examine the determinants of consumers' intention to reuse food delivery containers (ITR) using the extended theory of planned behavior (TPB). Moral obligation was included as an antecedent, while behavioral expectation (BE) ahead of behavioral intention was an immediate predictor of consumers' pro-environmental behaviors. Design/methodology/approach: The hypotheses were tested on 348 food delivery service users in Malaysia and analyzed using the partial least squares structural equation modeling (PLS-SEM). Findings: The findings indicated that consumers' ITR is directly influenced by perceived behavioral control and attitude. Perceived behavioral control and attitude had a positive partial indirect effect on ITR through BE. Meanwhile, subjective norms and moral obligation had a positive full indirect effect on ITR through BE. Research limitations/implications: The findings can be directly applied to practical situations of food delivery companies and environmental protection organizations managing solid waste among food delivery services. Practical implications: Understanding consumers' ITR could promote practical environmental sustainability. Practically, the study provides insights to the food delivery service industry, policymakers and relevant stakeholders to encourage consumer behavior change by reusing food delivery containers in line with Sustainable Development Goal 12. Originality/value: The study enhances the existing literature by extending TPB with two psychological variables: moral obligation (independent variable) and BE (mediating variable). To the best of the authors' knowledge, this study is the first attempt to empirically investigate BE in consumers' pro-environmental behavioral intention in a high-context culture and developing economy. This study could benefit food and beverage merchants, food delivery companies, governments, non-governmental organizations and pro-environmental behavior researchers in this industry.